Pengaruh iradiasi ultraviolet (254 nm) terhadap pelemahan kemampuan menginfeksi mirasidium Fasciola gigantica - Edy Riwidiharso; Billalodin Billalodin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
The controlling of fascioliasis has not been satisfying so far, since the effort of breaking off the fluke life cycle often leads to resistance. The resistance is due to the synchronization between the parasites and their snail host and high infection ability of the parasites enabling them to finish their life cycle. Ultraviolet irradiation provides alternative approach possibly applied to cope with the resistance. The objectives of this research were to know the ability of F. gigantica miracidium in infecting Lymnaea sp. at various ages and  to determine time exposure of ultraviolet (254 nm) effectively reducing the ability of miracidium infection. The results indicated that susceptible age of Lymnea javanica is five weeks old, while the most effective time exposure of ultraviolet (254 nm) in weakening  the ability of Fasciola gigantica miracidium infection to L. javanica is 60 seconds (P < 0,05).  At the moment the study on reinfection effect of F. gigantica miracidium on the immunity of L. javanica is still in progress.